PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN DIVIDENDENGAN LIKUIDITAS SEBAGAI VARIABEL MODERASI - Vania Alif Firdaus; Arie Indartono; Ristanti Akseptori (Proceeding Maritime Business Management Conference, 2023)
This study was conducted to determine the effect of profitability (ROA) on dividend policy (DPR) with liquidity (CR) as a moderating variable in infrastructure sector companies, and the transportation & logistics sector on the Indonesia Stock Exchange for the period 2018- 2022. The sampling method in this study was purposive sampling and obtained 8 samples that met the criteria from 92 companies. The type of data used is secondary data obtained from www.idx.co.id. This data was analyzed using Moderated Regression Analysis (MRA). The results of the study Liquidity weakens the influence of Profitability on Dividend Policy. Suggestions that can be conveyed for investors who will invest their funds are advised to be more careful in analyzing and paying attention to the company's financial performance so that they are not affected by the apparent increase in dividend payments.